Extent and Experience of Cyberbullying in Primary and Lower Secondary Grades During the First Quarantine of COVID-19 Pandemic - Buzaitytė Kašalynienė, Jolita; Žėkaitė, Jovita; Jusienė, Roma; Stonkuvienė, Irena (Pedagogika, 2023)
The article analyses the extent and experiences of cyberbullying among pupils from primary and lower secondary schools during distance education. The research is conducted using the qualitative and quantitative research from June to December of 2020. The data analysis is presented in the article. The research samples included parents of pre-primary children and 1st-8th formers, teachers, and 5th-8th formers. The quantitative research results show that the extent of bullying decreased during the spring quarantine (7 per cent), whereas bullying increased in the autumn when pupils returned to schools for contact lessons (20 per cent). The qualitative research allowed to disclose pupils’ experiences related to bullying and adults’ (teachers and parents) reactions to it. It is supposed that less bullying was recorded during the period of distance education because it was easier for the pupils to avoid bullying online and because teachers noticed fewer manifestations of bullying as the way of communication changed. Moreover, pupils could not have reported bullying to the adults because of socio-cultural norms existing in the environment, which claim that bullying is “a natural” process in adolescence, which a pupil has to live through.